Bacillus subtilis Protects Porcine Intestinal Barrier from Deoxynivalenol via Improved Zonula Occludens-1 Expression - Gu, Min Jeong (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2014)
Intestinal epithelial cells (IECs) forming the barrier for the first-line of protection are interconnected by tight junction (TJ) proteins. TJ alteration results in impaired barrier function, which causes potentially excessive inflammation leading to intestinal disorders. It has been suggested that toll-like receptor (TLR) 2 ligands and some bacteria enhance epithelial barrier function in humans and mice. However, no such study has yet to be claimed in swine. The aim of the present study was to examine whether Bacillus subtilis could improve barrier integrity and protection against deoxynivalenol (DON)-induced barrier disruption in porcine intestinal epithelial cell line (IPEC-J2). We found that B. subtilis decreased permeability of TJ and improved the expression of zonula occludens (ZO)-1 and occludin during the process of forming TJ. In addition, ZO-1 expression of IPEC-J2 cells treated with B. subtilis was up-regulated against DON-induced damage. In conclusion, B. subtilis may have potential to enhance epithelial barrier function and to prevent the cells from DON-induced barrier dysfunction.